WNK1 pathway and its role in regulating hypertension - Alessi, Dario (Henry Stewart Talks, 2011)
Mutations in WNK kinases cause familial hypertension, WNK1 interacts with and activates SPAK and OSR1, Physiological functions of SPAK and OSR1, Hyperosmotic conditions affect NKCC1 via WNK1 and SPAK/OSR1, A suggested mechanism of action for Thiazide diuretics in Gordon's syndrome patients, How the WNK pathway regulates blood pressure-a current model, Defining physiological roles of SPAK in knock-in mice, MO25 also regulates the activity of SPAK/OSR1, Functions and schematic representation of LKB1 and SPAK/OSR1 protein complexes